Practicing Social Isolation During a Pandemic in Brazil: A Description of Psychosocial Characteristics and Traits of Personality During COVID-19 Lockout - Zanini, Daniela Sacramento; Peixoto, Evandro Morais; Andrade, Josemberg Moura de; Tramonte, Lucia (Frontiers in Sociology, 2021)
The experience of the pandemic caused by the Coronavirus and the consequent disease triggered by it (COVID-19) brought to light fragilities that have been long overlooked by the scientific community and social institutions. The pandemic also showcased reactive social practices and phenomena resulting from individual behaviors, especially wearing a mask or practicing social isolation and stressed the need for social commitment and pro-social behaviors to face it. The purpose of this article was to evaluate psychological and sociodemographic characteristics associated with social isolation and health care in two different moments of the pandemic experience in Brazil: in the first month and after three months. Participants were recruited through advertisements in the media and social networks. 1,914 individuals aged between 14 and 81 years, 78.2% of which women, from 25 Federative Units in Brazil participated in the first phase of the study. In the second phase, 761 individuals participating in the first phase were reassessed. The authors deployed the following instruments for data collection: a standardized questionnaire collecting information of sociodemographic characteristics and dynamics of social isolation; the Kessler Psychological Distress Scale; the Life Satisfaction Scale; the Positive and Negative Affections Scale; and the Reduced Personality Markers and Stress Mindset Scale. All instruments used presented evidence of validity and adequate reliability indexes. The comparison of categorical exploratory variables with motives for doing social isolation was performed using Pearson's Chi-square and the comparison of continuous exploratory variables was performed using the Mann-Whitney test. Covariance Analysis was performed using covariates those that showed significance/effect on isolation in previous analysis. The results showed that respondents practicing social isolation to comply with governmental recommendations had lower scores on the scales of neuroticism and consciousness; they reported less stress, anxiety, and depression, and less general distress. Overall, these respondents also displayed more positive affect, and tended to reframe stress in a more positive way than others. These preliminary results point to the importance of considering the psychological characteristics and their influence on the social behavior of individuals and on supportive (pro-social) behavior, even in a period of significant stress and high social risk.